Trombofilias e Contracepção - Machado, AI (2008)
Thrombophilias, whether inherited or acquired, are a topic of increased interest in women’s health. Factors that enhance thrombus formation in the presence of thrombophilia include oral contraception, hormone replacement therapy, pregnancy and the puerperium. The risk of venous thomboembolism with hormonal contraceptive use is greater in women with underlying thrombophilias, and thrombosis usually occurs earlier than in women without defined thrombophilias. The degree of increased risk varies according to the underlying thrombophilic defect, the largest bulk of evidence referring to women with Factor V Leiden or prothrombin gene mutation. However, most instances of thrombosis occur due to a combination of inherited, acquired and environmental factors. Before starting oral contraception it is important to screen patients to identify those at increased risk of thrombosis.